The structure of evolutionary theory - Gould, Stephen Jay (Cambridge, Mass. : The Belknap Press of Harvard University Press, 2002)
The world's most revered and eloquent interpreter of evolutionary ideas offers a work of explanatory force unprecedented in our time--the history and origins of the three core commitments of classical Darwinism.
Ch. 8-12: Towards a revised and expanded evolutionary theory.
Keywords: teorija evolucije